One-Dimensional Statistical Parametric Mapping Identifies Plantar Regional Loading Differences Related to Medial Longitudinal Arch Stiffness - Cen, Xuanzhen; Song, Yang; Biro, Istvan (Proceedings (International Conference on Computer Engineering and Applications. Online), 2023)
Statistical parameter mapping (SPM) as a statistical test based on spatio-temporal smoothing and data normalization has been widely employed in computer engineering and biomechanical research. The present study aimed to analyze the influences of different medial longitudinal arch stiffness on the differences in gait plantar loadings by computer-based one-dimensional SPM. Fifty-four asymptomatic male subjects were recruited for the study based on the results of the G*Power analysis. A foot scanner was employed to acquire three-dimensional foot morphology under different load conditions for the calculation of arch stiffness. The dynamic plantar pressure data were collected from the ten plantar anatomical regions during the gait task. The results indicated that individuals with more flexible medial longitudinal arches experienced significantly increased plantar loading in the toe, medial metatarsal, and hindfoot regions during gait while significantly lower in the midfoot region. Combined with the SPM & SnPM statistics, this recorded dataset of time-series plantar region loading variability caused by differences in arch stiffness is essential for the interpretation of foot biomechanical function and injury prediction associated with arch morphology.